The cultures of knowledge organizations : knowledge, learning, collaboration (KLC) - Kucharska, Wioleta, 1977-; Bedford, Denise A. D., 1950- (Emerald Publishing Limited, 2023)
Organizations are increasingly aware of the role that culture plays in implementing strategies. The adage "culture eats strategy for breakfast everyday' shows how important it is to understand, monitor, and calibrate company culture. This means shaping the behaviour of leaders, managers, teams, and individuals. It means integrating assessment and behaviours into performance and communication strategies. Cultures - at all levels - are shifting in today's society. It is important to understand which factors are having which effects. The Cultures of Knowledge Organizations presents a new perspective that treats organizational culture not as a static conceptual model but as a dynamic, complex and adaptive system. The authors consider how de facto organizational business cultures must function in a hyperdynamic knowledge economy. Today's managers need real practical guidance on how to see "culture', how to assess it, how to design a culture that supports business goals, and how to help the workforce understand their own role in shaping culture. This research acts as a map for 21st Century.
Keywords: Corporate culture.; Organizational behavior.; Business & Economics, Workplace Culture.; Organizational theory & behaviour.; elektronické knihy; electronic books